Performance analysis of low earth orbit (LEO) satellite link in the presence of elevation angle, fading and shadowing - Farah, Tanjila; Roy, Priyanka (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.